Study on pollutant emission inventory of port. Issue 1 (April 2021) - Guo, Xu; Xu, Da
Abstract: With the frequent exchanges of Global trade, ports play an increasingly important role in economic development. However, the environmental problems caused by the port are also increasing. As the most basic, comprehensive and practical information, emission inventory is the premise of scientifically formulating and improving the control measures and policies of pollutants from ships and ports. In this study, some terminals in coastal ports are taken as an example to provide technical support for port pollutant emission estimation and pollution control by compiling pollutant emission inventory..